2013
DOI: 10.1089/lrb.2012.0021
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Pump Treatment Repeatedly Enhances the Lymphatic and Immune Systems

Abstract: Background: Osteopathic practitioners utilize manual therapies called lymphatic pump techniques (LPT) to treat edema and infectious diseases. While previous studies examined the effect of a single LPT treatment on the lymphatic system, the effect of repeated applications of LPT on lymphatic output and immunity has not been investigated. Therefore, the purpose of this study was to measure the effects of repeated LPT on lymphatic flow, lymph leukocyte numbers, and inflammatory mediator concentrations in thoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…More recently, preliminary lab-based evidence showed the effect of specific osteopathic techniques on the enhancement of the lymphatic and immune system [42,43] by improving the leukocytes count and interleukin-8 (IL-8). Findings were confirmed by a research article published in 2014 where significant differences were detected in the levels of immune molecules, including IL-8, between OMT and sham light-touch control.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, preliminary lab-based evidence showed the effect of specific osteopathic techniques on the enhancement of the lymphatic and immune system [42,43] by improving the leukocytes count and interleukin-8 (IL-8). Findings were confirmed by a research article published in 2014 where significant differences were detected in the levels of immune molecules, including IL-8, between OMT and sham light-touch control.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lymphatic intrinsic pumping function is considered important for maintaining the homeostasis of interstitial fluid and molecule balances in local tissue and may be critical for total body health, 3,4 the effect of reduced lymphatic pumping pressure (P lp ) in the legs on general health has not been studied. Many people complain of leg edema in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LPT has been shown to enhance 12 and increased the lymphatic flux of leukocytes, cytokines, and reactive oxygen and nitrogen species. 17,18 Collectively, these studies suggest that LPT can stimulate the lymphatic and immune systems, which may accelerate the removal of pneumonia by the immune system. In support, lymph can activate leukocytes, 25 increase endothelial cell permeability, 26,27 and redistribute leukocytes, cyto- LPT can be optimally applied to patients with pneumonia, which may substantially reduce morbidity, mortality, and the cost of hospitalization.…”
Section: Effect Of Lpt On Hematologic Factorsmentioning
confidence: 93%
“…9 To our knowledge, no reports have been published measuring the effects of LPT on the lymphatic system in humans, but animal studies have demonstrated that LPT yields significant (P<.05) increases in lymph flow and in the lymphatic concentration of leukocytes. [11][12][13][14][15][16][17][18] In these studies, LPT did not preferentially mobilize any specific immune cell population, but it significantly (P<.05) increased thoracic duct lymph flow and total leukocyte concentrations, resulting in an approximately 10-fold increase in the lymphatic flux. 12 Lymphatic pump treatment also significantly (P<.05) enhanced the lymphatic flux of inflammatory cytokines, chemokines, and reactive oxygen and nitrogen species in both thoracic and mesenteric lymph, 17,18 and it enhanced the uptake of protein from the tissue's interstitial space.…”
Section: Animalsmentioning
confidence: 99%